2019
DOI: 10.31590/ejosat.545139
|View full text |Cite
|
Sign up to set email alerts
|

Kısıtlar Teorisinde Kapasite Kısıtı ve Bir Üretim İşletmesinde Uygulaması

Abstract: Öz İşletmelerin karlılık hedeflerine ulaşabilmeleri için müşterilerinin taleplerini mümkün olduğunca hızlı, zamanında ve istenilen miktarlarda karşılamaları gerekmektedir. Aksi halde müşteri ve prestij kaybı yaşanabilir. Müşterilere zamanında, istenen miktarda ürün verebilmenin yollarından biri kapasitenin (iş gücü, makine, çalışma saati vb.) yeterli olabilmesidir. Bu çalışmada Kısıtlar Teorisi üzerinde durulmuş ve çalışma, kapasite kısıtı üzerine temellendirilmiştir. Kısıtlar Teorisi, işletmenin hedeflerine u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…Antmen and Erik (2019) concluded that the current profitability of the business increased approximately thirty-seven times by using the constraints theory and break-even analysis together in their study. Akçimen and Antmen (2019) concluded in their study that the production process created according to the constraints theory in a manufacturing enterprise operating in the metal sector can increase the profitability of the enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Antmen and Erik (2019) concluded that the current profitability of the business increased approximately thirty-seven times by using the constraints theory and break-even analysis together in their study. Akçimen and Antmen (2019) concluded in their study that the production process created according to the constraints theory in a manufacturing enterprise operating in the metal sector can increase the profitability of the enterprise.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been seen that studies in the literature about the TOC are conceptual, the application of TOC principles to different theoretical problems, the comparison of TOC philosophy with different systems and TOC applications (Rahman, 1998). The TOC has been applied to many fields; the manufacturing sector (Ünal, Tanış & Küçüksavaş, 2005;Demircioğlu & Akkaya, 2016;Wolniak, Skotnicka-Zasadzien, & Zasadzien, 2018;Urban & Rogowska, 2018;Rojas, Jurado, & Londono, 2018;Sorkun, 2018;Urban, 2019;Garza, et al, 2019;Akçimen & Antmen, 2019;Aiastui, Perez de Eulate, & Guisasola, 2020;Al-Fasfus, Hamza, & Elkotayni, 2020;Karakoç & Şık, 2021;Mahdi, Abboud & Hussain, 2021), the service sector (Taştan & Demircioğlu, 2015;Akbulut & Ertan, 2015;Ayanoğlu & Şakar, 2015;Yükçü & Yüksel, 2015;Escobar, Vega, & Zamora, 2016;Grida & Zeid, 2019), supply chains (Harish, 2019;Kelly & Germain, 2020;Huang, Lu & Dang, 2021), project management (Mishra, 2020;Sarkar, Jha & Patel, 2021), product mix decisions (Ünal et al, 2005;Kaygusuz, 2005;Mehdizadeh & Jalili, 2018) and human resources management (Tekin & Şahin, 2014;Alghaithi & Sartawi, 2020). 6σ is a systematic approach that aims to increase business profitability, performance, production and customer satisfaction, as well as to reduce the operational costs of the business.…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle kalabalık ve sanayileşmiş şehirlerde sanayinin su kullanımı en yüksek seviyededir. Zaman ilerledikçe, teknoloji geliştikçe; müşteri ihtiyaç ve beklentileri artmakta dolayısı ile yöneticilerin de istekleri değişmektedir (Akçimen & Antmen, 2019). Bu da daha fazla suyun kullanımına yol açabilmektedir.…”
Section: Introductionunclassified